Environmental Risks Related to the Recovery and Recycling Processes of Waste Electrical and Electronic Equipment (WEEE) - Generowicz, Agnieszka; Iwanejko, Ryszarda (Problemy Ekorozwoju, 2017)
The idea of sustainable development imposes waste management tasks that can be solved only using a systemic approach. It requires that municipal waste management is carried out in a technically correct manner, is economically efficient, socially acceptable, with no negative effect to the natural environment and takes into account economy of all waste streams, including electrical and electronic waste (E-waste). A relentless pursuit of comfort, quality of life as well as rapid technological changes result in products of a shorter life cycle, which quickly become just electro scraps. There are many of them with a different composition. E- waste may include e.g. toxic metals, which if released to the environment may pose a threat to human life and health. At the same time, recovery of valuable secondary raw materials complies perfectly with implementation of the principles of sustainable development. In recent decades, the risk assessment for the natural environment and decision-making strategies have become a target of intense and complex research undertaken also in the waste management area. The main objective of risk assessment is providing a rational basis to make unbiased decisions about the system. The article attempts to identify and assess risks of an environmental impact resulting from negligence or operational disturbances in a system of recovery and recycling of electrical and electronic waste.